Anxiety level of men's futsal players after experienced injury - Pamungkas, Galih; Sabillah, Muhamad Ichsan; Annasai, Faza; Humam, Muhammad Fatih (Jorpres (Jurnal Olahraga Prestasi), 2023)
This study aims to find out how high the anxiety level of Men's Futsal players is after experiencing an injury. This research is a descriptive research. The method used is a survey. The data collection technique uses a Google Form questionnaire. The population in this study was UNY's male Futsal players, totaling 33 people. Sampling in this research was carried out using purposive sampling. The criteria for determining this sample include: (1) willing to be a research sample, (2) willing to fill out the Google form happily, according to the existing reality, and (3) having experienced an injury. Based on these criteria, there were 26 players who met. The data analysis technique uses quantitative descriptive analysis presented in percentage form. The results of the study showed that the anxiety level of UNY Men's Futsal players after suffering an injury was in the "very low" category at 3.85% (1 person), "low" at 19.23% (5 people), "fair" at 46.15 % (12 people), "high" was 26.92% (7 people), and "very high" was 3.85% (1 person).